PENGARUH QUICK RATIO, RATIO HUTANG DAN PERPUTARAN PIUTANG TERHADAP ROA PADA TRADE COMPANY TAHUN 2015-2019 - Tannadi, Andy (2021)
The purpose of this study was to test whether the Quick Ratio, debt ratio and accounts receivable turnover had an effect on profitability (ROA) of the Trade Companies listed on the Indonesia Stock Exchange in 2015-2019 using the t test and F test. This study used a deductive, quantitative and descriptive approach. . The number of Trade Companies listed on the IDX is 65 companies and the sample that meets the criteria according to purposive sampling is 22 companies. The data processing technique used is multiple linear regression analysis. The results of this study indicate that partially Quick Ratio has no effect on ROA, the debt ratio (DER) has a negative effect on ROA and accounts receivable turnover has a positive effect on ROA. Simultaneous research results show that Quick Ratio, DER and accounts receivable turnover have a significant effect on ROA. The result of the determination coefficient test in the Adjusted R Square column shows the number 0.178, which means that 17.8% of the variation in profitability (ROA) can be explained by independent variables, the remaining 82.2% is influenced by other factors such as cash turnover, current ratio and working capital turnove